(untitled) (Journal of Social Sciences Review, 2023)
Online learning is one way for students to get the knowledge they need. Most schools around the world have switched to online learning, which means that students don’t see each other as much. This study analyzed how these factors were associated with and impacted each other. a quantitative approach to gathering data and analysing the effectiveness of online learning platforms. A cross-sectional study design is used to collect data at a specific point in time. The sample consisted of 500 university students who have experienced remote education through online learning platforms. The sampling technique combination of convenience sampling and stratified random sampling. The primary data collection method was a structured questionnaire. The questionnaire was designed to gather information about students’ perceptions and experiences with online learning platforms. The questionnaire was developed based on a review of the existing literature on online learning effectiveness The test results indicated that all the variables had a positive effect on the effectiveness of online learning. This showed that the more effective online learning was, the more benefits and positive outcomes the student experienced. The result of this research showed that learning objectives could enable universities to increase the effectiveness of students’ online learning by motivating students to join online classes and developing appropriate learning strategies for their individual needs.